The bank lending behaviour: Does non-performing loans matter? Evidence from the top-ten banks in the Arab world - Ahmed, Sayed Abbas; Sayed, Omer Ahmed; Ahmed, Ibrahim Elsiddig (Asian Development Policy Review, 2024)
This essay examines the third increase in non-performing loans (NPLs) in the Arab World, which the COVID-19 epidemic may have contributed to. This increase follows two previous waves that occurred in 1990 and after 2008. The primary aim is to analyze bank lending behavior, particularly examining the influence of firm-specific determinants on banks’ lending activities and the impact of NPLs on this behavior. Utilizing secondary data from 2016 to 2020, this research focuses on the top ten national banks in the Arab region. The methodology incorporates panel data derived from audited financial statements and employs OLS regression (Pooled) for analysis. The findings reveal a significant negative impact of NPLs and capital adequacy ratios on bank lending behavior, while bank size and deposit growth positively influence lending activities. Additionally, the study notes an insignificant relationship between profitability, equity as a percentage of total assets, and lending behavior. These results provide practical insights for banking sector decision-makers, emphasizing the management of NPLs through maintaining adequate capital, enhancing deposits, and increasing bank assets. From a social perspective, the study suggests that banks should prioritize lending to investors likely to fulfil their obligations, potentially limiting credit availability for smaller entities and individuals without guarantees. This approach aims to mitigate the risks associated with NPLs. This work’s originality lies in its concentration on a condensed sample that accounts for more than 70% of the banking resources in the Arab region, making it a significant contribution to applied research in this area that stands out for its reliance on pre-existing data.